Smart and Sustainable Cities: a brief critical reflection - Nobre, Raidete Maria Soares Fontes (2025)
Smart and sustainable cities use urban indicators, which serve as a basis for measuring, analyzing and understanding the context of cities. This study proposes to reflect on a topic of a global and modern nature, in addition to being extremely relevant, it is a brief critical reflection on the characteristics that chose smart and sustainable cities, with a focus on Salvador (BA). In this sense, the main objective is to critically reflect the common characteristics among the ten smart and sustainable cities in Brazil in 2024, with an emphasis on Salvador (BA), using a qualitative approach, the deductive method and the bibliographic procedure. The Google Scholar platform is used as a database. The study is justified as a result of critical reflection on the common characteristics of the ten smart and sustainable Brazilian cities, with a careful perception in Salvador. In the literature review process, it was noted that there are Public Policies and Programs that encourage cities to become smart and sustainable. There are also Rankings, making it possible to understand, compare and evaluate the progress of cities towards a more sustainable and intelligent future. In the 2024 edition, the Connected Smart Cities Ranking chooses Salvador (BA), the focus of this research, as the top 10. Although the Bahian capital was awarded among the ten smart cities, there is still a gap between this reality and the great challenges faced in other thematic axes, such as education, safety, health and environment.